Senderización y señalética turística de la cascada velo de novia y la cascada santa cleotilde de la Parroquia Tutupali del cantón Yacuambi provincia de Zamora Chinchipe - Sarango Medina, Maritza Alexandra (2016)
In Ecuador the Senderización and Tourism Signage is governed through the Ministry of Tourism hand to offer tourist destinations which owns the country and this has grown steadily generating new trends that have developed in the territories in recent years also required to generate conditions to facilitate travel and ensure visitors get to your destination. The province of Zamora Chinchipe consists of nine cantons and one of them is the Yacuambi canton where the Tutupali parish is the same that has not been potentiated or adequately promoted not because it has the respective senderización and tourist signposting due to absence of a study of the sector to implement this project, which produces the interest waterfall called Bridal Veil waterfall and the Holy Cleotilde are not marked. For this reason has been to pose next topic Titled: Senderización and Tourism Signage Veil Bride and waterfall Waterfall "Holy Cleotilde of the parish Tutupali Yacuambi Canton province of Zamora Chinchipe." For this purpose the following objectives: To make a diagnosis of the current situation of the Tutupali parish Yacuambi Canton Province of Zamora Chinchipe, develop the proposal Senderización and Tourism Signage for natural attractions Waterfall Bridal Veil and The Holy Cleotilde waterfall and Finally Identify potential significant environmental impacts that may occur at all stages of the project. Development goals synthetic, analytical, deductive and inductive method was used, the same who helped analyze all bibliographic results the same as that provided extra information to conclude with the diagnosis of the parish, and as a result information was obtained accurate and true research site. Then the methodology Carla Ricaurte, methodology MINTUR and direct observation technique was used, the same one that allowed us to determine the current status of the parish and therefore the records inventory and ranking of tourist attraction that allowed to know the natural wealth was obtained Tutupali of the parish; besides the interview technique was applied, also a SWOT analysis and identifying the internal and external factors allowing the parish to demonstrate the advantages and disadvantages that the sector has made. Also gathering information on the trails with GPS coordinates where geographical distances and the study area was obtained and concluded with the proposal of tourist signage planimeter designing the map of the trail was made. He then proceeded to take the load capacity of the trails using the methodology of Miguel Cifuentes where the maximum number of people can take to avoid disruption in the environment was established; Likewise the chips of the proposed signaling using manual force signposting of Ecuador was developed. Similarly qualitative cause-effect matrix Leopold where the activities to be held during the stages of the project was established developed. Similarly, the assessment of the impacts that may occur during project implementation through the rubric of Leopold with respect to (physical, biotic and socioeconomic) environmental factors that will be affected by the activities during the stage was construction, operation, maintenance and closure; and finally an environmental management plan for affected if the project were to run area was made. Among the findings it was considered that the Bridal Veil and Santa Cleotilde waterfalls have a scenic and natural beauty where visitors can enjoy all the wonders offered by this site and now the parish and cantonal GAD do not have enough budget to undertake tourism projects that help to improve the tourist conditions, it is noteworthy that one of the advantages of the parish is that the two waterfalls are located near the road axis allowing tourists to easily reach the destination. For this reason the Community and its authorities, as members representatives of Tutupali work on projects to promote and disseminate the attractions, as well as the provincial government of Zamora Chinchipe and cantonal government is recommended to prioritize the budget for tourism projects to promote management and thus improve the road infrastructure for better results in the tourism field.